ADAPTASI SOSIAL SISWA BARU DALAM MEMATUHI NORMA KEDISIPLINAN DI SEKOLAH USAHA PERIKANAN MENENGAH NEGERI PONTIANAK - Wallia Amiyanda; Amrazi Zakso; Rustiyarso Rustiyarso (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research is to know the disciplinary norms in the Pontianak State Fisheries Business Middle School. Qualitative phenomenological research methods. The source of research data from grade I students consisted of four female students and two male students and two BK teachers. With the acquisition of observation data and student activity interviews during school. The results showed that the student's social adaptation process was going well, the students were able to overcome obstacles and were able to participate in activities well according to the school discipline manual. The inhibiting factors for the social adaptation of new students are seniority, loss of indigenous culture, feeling the difference between a house and a dormitory, and the inability to respond to rules effectively. The supporting factors for social adaptation of new students are a sense of peace and interaction between students, flexibility and openness with the teacher so that they have tolerance and solidarity to maintain the applicable rules to survive through a period of mutual adaptation. It can be concluded that the social adaptation of new students with semi-military school discipline rules, minority and punishment does not affect the quality and mental improvement of students.Keywords: Social Adaptation, Norm Discipline, SUPM, Pontianak